A Phylogeny and Classification of the Amphipoda with the establishment of the new order Ingolfiellida (Crustacea: Peracarida) - Lowry, J.k.; Myers, A.a. (Zootaxa, 2017)
A classification is proposed for the order Amphipoda. The Amphipoda includes six suborders, the Pseudingolfiellidea, Hyperiidea, Colomastigidea, Hyperiopsidea, Senticaudata (described in a previous contribution (Lowry & Myers 2013)) and Amphilochidea. The suborder Ingolfiellidea is raised to order status. A cladistic tree, based on morphology, is presented illustrating the relationships of the Amphipoda at parvorder level. A tree for the families of the Physomatidira and Physocephalatidira, a tree for the Maxillipiidira, Oedicerotidira, Eusiridira and Amphilochidira and a tree for the Synopiidira, Haustoriidira and Lysianassidira, are provided. Families are listed together with their included genera. New families are diagnosed.